An Exploration into the Application of Human-in-the-Loop Technologies for Personalised Music Recommendation - Ellis, Christopher (2020)
The evolution of the internet over the last 30 years has drastically changed the way we find and consume music. Today we can get near-instantaneous access to vast libraries of music with streaming services like Spotify offering archives in excess of 30 million tracks. Faced with such overwhelming choice it can be easy to become paralysed by the possibilities. We need some automated and effective means of navigating this sea of content to identify the music we want.